Corporate governance during financial distress – an empirical analysis. Issue 5 (12th September 2016) - Parkinson, Marjan Marandi
Abstract : Purpose: The traditional form of legal research with its predominant emphasis on doctrinal and theoretical analysis is now increasingly augmented by empirical research that seeks to document actions and decisions and draw broader conclusions. This relatively new research tradition is arguably making a positive contribution to legal theory and practice, particularly in the USA [for a general discussion see SJ Lubben, "Do Empricial Bankruptcy Studies Matter?" (2012) 20 ABI L Rev 715]. The paper aims to report on the use of empirical research to examine corporate governance in the context of financially distressed UK public companies. Design/methodology/approach: The paper uses statutory corporate filings and mandatory stock exchange reports to document the process of informal debt resolution prior to the company's entry into administration or Company Voluntary Arrangement. The findings are presented in an innovative way as a series of case studies focusing on process, participants and outcomes of informal debt resolution. Findings: The paper concludes that it is possible to use case study research as a means to explore corporate governance in the context of financially distressed companies. Although such an approach is challenging in various ways, there are some advantages that complement more traditional research approaches. The findings show how directors' attention shifts away from shareholders' interests to those of creditors at times of financial distress and challenges conventional models of governance that stress shareholder value. Originality/value: The distinctive features of the research are the development of a case-study based approach that draws on publicly available data sources, a process based analysis and a synthesis of corporate governance and law.